2019
DOI: 10.1101/778969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Predictions: Oscillatory Mechanisms Underlying Multisensory Sequence Processing

Abstract: Neural oscillations have been proposed to be involved in predictive processing by frequencyspecific modulation of either power or phase. While this is supported by substantial evidence on unimodal processing, only few studies are currently available that have addressed the role of oscillatory activity in multisensory predictions. In the present study, we have recorded MEG during a serial prediction task in which participants had to acquire stimulus sequences and to monitor whether subsequent probe items compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(85 reference statements)
2
1
0
Order By: Relevance
“…Here, fixed word orders contained linear order-based cues, which are analogous to English, while flexible word orders required animacy-based cues for interpretation. From this perspective, and in line with previous work on sequence processing (Crivelli-Decker et al, 2018; Kikuchi, et al, 2018; Wang et al, 2019), increased beta power likely reflected the propagation of top-down predictions during the learning of fixed word orders (Cross et al, 2018). In fixed sentences, the first noun is invariably the Actor, and as such, predictions are constrained to anticipating that the second noun will be the Undergoer, while also containing a verb-final construction.…”
Section: Discussionsupporting
confidence: 81%
“…Here, fixed word orders contained linear order-based cues, which are analogous to English, while flexible word orders required animacy-based cues for interpretation. From this perspective, and in line with previous work on sequence processing (Crivelli-Decker et al, 2018; Kikuchi, et al, 2018; Wang et al, 2019), increased beta power likely reflected the propagation of top-down predictions during the learning of fixed word orders (Cross et al, 2018). In fixed sentences, the first noun is invariably the Actor, and as such, predictions are constrained to anticipating that the second noun will be the Undergoer, while also containing a verb-final construction.…”
Section: Discussionsupporting
confidence: 81%
“…Here, fixed word order sentences contained linear order-based cues, which are analogous to English, while flexible word orders required animacy-based cues for interpretation. From this perspective, and in line with previous work on sequence processing (Crivelli-Decker et al, 2018;Kikuchi, et al, 2018;Wang et al, 2019), beta synchronisation likely reflected the propagation of top-down predictions during the learning of fixed word order rules. Specifically, in fixed sentences, the first noun is invariably the Actor, and as such, predictions are constrained to anticipating that the second noun will be the Undergoer, while also containing a verb-final construction.…”
Section: Neural Oscillations Language Learning and Sentence Processingsupporting
confidence: 79%
“…Previous research examining spectral dynamics during (artificial) language learning has revealed that increased alpha/beta power (i.e., synchronisation) predicts sensitivity to grammatical violations (Kepinska et al, 2017), while increased gamma phase coherence between frontal, temporal and parietal cortices is associated with successful learning (De Diego-Balaguer et al, 2011). An increase in theta synchronisation is also associated with poorer learning of auditory rules (De Diego-Balaguer et al, 2011).During visual grammar learning, theta synchronisation increases early in the task and declines after prolonged exposure (Kepinska et al, 2017).While these findings are inconsistent with images and word stimuli, studies using complex sequence processing have reported linear increases in beta power for predicable sequences, which coincide with increased theta activity in task-related cortical regions (Crivelli-Decker et al, 2018;Wang et al, 2019), and occipital alpha power (Wang et al, 2019). These data are also in line with the supposed role of active, top-down mechanisms in the processing of incoming sensory input, akin to a predictive-coding account of brain function (Friston, 2010;Kikuchi et al, 2018;Rao & Ballard, 1999).…”
Section: Oscillatory Correlates Of Artificial Language Learningmentioning
confidence: 99%